Evaluation of diagnostic accuracy of conventional and digital periapical radiography, panoramic radiography, and cone-beam computed tomography in the assessment of alveolar bone loss - Wilton Mitsunari Takeshita; Lilian Cristina Vessoni Iwaki; Mariliani Chicarelli Da Silva; Renata Hernandes Tonin (Wolters Kluwer Medknow Publications, 2014)
Background: To evaluate the diagnostic accuracy of different radiographic methods in the assessment of proximal alveolar bone loss (ABL). Materials and Methods: ABL, the distance between cement-enamel junction and alveolar bone crest, was measured in 70 mandibular human teeth - directly on the mandibles (control), using conventional periapical radiography with film holders (Rinn XCP and Han-Shin), digital periapical radiography with complementary metal-oxide semiconductor sensor, conventional panoramic, and cone-beam computed tomography (CBCT). Three programs were used to measure ABL on the images: Image tool 3.0 (University of Texas Health Sciences Center, San Antonio, Texas, USA), Kodak Imaging 6.1 (Kodak Dental Imaging 6.1, Carestream Health ® , Rochester, NY, USA), and i-CAT vision 1.6.20. Statistical analysis used ANOVA and Tukey's test at 5% significance level. Results: The tomographic images showed the highest means, whereas the lowest were found for periapical with Han-Shin. Controls differed from periapical with Han-Shin (P < 0.0001). CBCT differed from panoramic (P = 0.0130), periapical with Rinn XCP (P = 0.0066), periapical with Han-Shin (P < 0.0001), and digital periapical (P = 0.0027). Conventional periapicals with film holders differed from each other (P = 0.0007). Digital periapical differed from conventional periapical with Han-Shin (P = 0.0004). Conclusions: Conventional periapical with Han-Shin film holder was the only method that differed from the controls. CBCT had the closest means to the controls.